PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA - Tyra, M.J; Sarjono, Andreas (Catholic University Musi Charitas, 2020)
The research entitled The Effect of Entrepreneurship Education on Entrepreneurial Interest (Survey on Students of Management Studies Program at the Catholic University of Musi Charitas) was a study to prove whether entrepreneurship education influences students of Management Studies Program at the Catholic University of Musi Charitas for their interest in managing a business. Because this problem remains a question whether the education obtained and the business practices that have been carried out had an impact on student interest in opening a business. The variables used were Entrepreneurship Education variable (X) including Know-What, Know-Why, Know-Who, and Know-How indicators. While for variable Y was the interest in entrepreneurship. The type of research used was survey technique. Data collection techniques were carried out by distributing 5-point Likert scale questionnaires, that is from strongly disagree to strongly agree. The population in this study was active students of Management Study Program at the Catholic University of Musi Charitas who had taken entrepreneurship courses at Batch 2017/2018 and 2018/2019. The sampling technique used was census technique. The data analysis technique used was descriptive analysis with an average score calculation, and the Research Hypothesis regression testing was using simple regression analysis. The results of the study through t-test from simple proved that entrepreneurship education influences the interest in entrepreneurship with a significance value of 0.001 (<0.005).